Landscape management in tropical regions based on an assessment of ecosystem services - Hashim, Mazlan; Yoshida, Keiichiro; Ibrahim, Ab. Latif; Okuda, Toshinori; Bongkik, Mahdan; Rani, Roslan (National Institute for Environmental Studies, Japan, 2003)
This study reports the assessments of economic values of ecological services (EVSG) at Pasoh Forest Reserve (PFR), Malaysia. A model was proposed for landscape management that encompasses the least economic risk. The specific objectives of this study are: (1) to estimate the EVSG delivered by a biome when it is relatively intact, and when it has been converted to other land uses, including logging and oil palm plantations; (2) to compare the economic value of tropical forest with alternative land uses and evaluate the economic risks of deforestations in PFR; (3) to develop appropriate land use model base on a composition of the economic values of both ecosystem services and commercial products from tropical forests, logged forests, and oil palm plantations using a spatial-based model.